COMPREENSÃO DA QUALIDADE DE VIDA EM PACIENTES ONCOLÓGICOS: UM ESTUDO LONGITUDINAL SOBRE DESAFIOS PSICOEMOCIONAIS E SAÚDE FÍSICA. (CIPEEX, 2026)
Introduction: Cancer represents a public health problem with physical, emotional, and social repercussions, requiring a comprehensive assessment of quality of life. Objective: To investigate, in an integrated manner, the physical health, psychoemotional aspects, and level of independence of patients undergoing cancer treatment. Methodology: Descriptive, quantitative study with 95 patients, using the WHOQOL-bref and a sociodemographic questionnaire. The analysis was performed in SPSS 25.0, with statistical tests (p ≤ 0.05). Results: Pain was the main limiting factor, followed by fatigue and sleep disorders. Mobility was the most preserved physical aspect. Patients with children had lower scores in the psychological domain, while the practice of physical/cultural activity was associated with better emotional well-being. Better global health conditions correlated with higher scores in both domains (p < 0.05). Conclusion: The results reinforce the need for multidisciplinary management, including symptom control, psychological support, and encouragement of practices that promote autonomy, aiming to optimize the overall quality of life of patients.
Keywords: cancer; Quality of Life; Oncological treatment